Empowering High School Students with Software-Based Mathematical Skills for College and Career Readiness - Megantara, Tubagus Robbi; Hidayana, Rizki Apriva; Nurkholipah, Nenden Siti; Amelia, Rika; Syarifudin, Abdul Gazir; Mulyo, Lukman Widoyo; Khan, Muhammad Fardeen; Agustin, Nemia (International Journal of Research in Community Services, 2025)
In the current data-driven era, data literacy is a critical competency, yet many high school students lack practical training in essential software like Microsoft Excel, creating a significant skills gap. To address this challenge, the Mathematics Study Program at Universitas Kebangsaan Republik Indonesia conducted a community service program designed to empower high school students with foundational data analysis and visualization skills through a structured, hands-on Excel workshop. The program employed a phased approach, beginning with a socialization session for 31 students, followed by an intensive training workshop for a final cohort of 12 students. The workshop was segmented into three progressive modules: Foundations of Data Management, Logical Analysis and Data Interpretation, and Data Visualization. The program's effectiveness was evaluated using qualitative performance-based assessments and a feedback survey to measure changes in skill and confidence. The results indicate that the training was highly successful, demonstrably improving participants' competence and confidence as evidenced by overwhelmingly positive survey feedback. The foundational and data visualization modules were particularly effective, while the module on logical functions was identified as the most significant challenge for students. This initiative not only succeeded in delivering essential digital skills for college and career readiness but also offered valuable pedagogical insights, confirming the effectiveness of hands-on workshops and highlighting areas for refinement in technical education.